Persepsi Karyawan Terhadap Penggunaan Teknologi Informasi Pada Hotel Sintesa Peninsula Manado - Tiara Anggita Regar; William A. Areros; Sandra I. Asaloei (JURNAL ADMINISTRASI BISNIS, 2018)
The purpose of this study is to analyze and describe the perceptions of the usefulness of information technology, perceptions of ease of information technology, attitudes, behavioral intentions, and behavioral use of information technology. The research benefits are as a contribution to the study of the use of information technology and human resource development. Utilization of information technology in the business world enables companies to have high competitiveness, which in turn allows the success of achieving the expected benefits. The use of information technology is influenced by many factors, among others by the perception of its users. This research uses descriptive method with analysis technique of frequency distribution and percentage. The data used is a statement of perception about the usefulness of information technology, ease of information technology, attitude, intention and behavior, obtained through questionnaires with Likert scale. The results of this study indicate that employees of Hotel Sintesa Peninsula Manado perceive the use of information technology is very supportive of the implementation of the task. They believe the use of information technology is very useful in the implementation of work. Employee perception is related to the usefulness of information technology, ease of use of information technology, attitudes toward information technology, behavioral intent to use information technology, and behavioral use of information technology. There is no difference in perception because of differences in sex, age, and education level.